The role of RETN in stomach adenocarcinoma (STAD): insights from pan-cancer analysis of RNA-seq data based on the TCGA database - Yaxing Deng; Chenglin Wang; Rui Yang; Qingqiang Yang (Discover Oncology)
Abstract Objective To analyze the expression and significance of resistin (RETN) in pan-cancer and determine the prospect of RETN as a biomarker for STAD, providing a new diagnostic and therapeutic target for STAD. Methods Based on the RNA-seq data from the TCGA database, RETN was comprehensively analyzed from the perspective of pan-cancer. Firstly, the expression of RETN, correlation of immune infiltration, diagnostic efficacy and prognostic value in pan-cancer were investigated. Subsequently, the potential value of RETN as a biomarker for STAD was evaluated. Finally, the potential mechanisms of RETN in STAD were explored, including single-cell expression, PPI, functional enrichment analysis, single-gene correlation, gene co-expression analysis, and immune infiltration correlation. Results RETN is upregulated in most tumors and is associated with a variety of immune cells. As a potential biomarker, RETN showed good diagnostic efficacy and prognostic value in a variety of tumors. The prediction model based on pathological stage, sex, age and RETN has a good prediction effect on the overall survival of STAD patients. Single-cell expression analysis showed that RETN was mainly expressed by DC cells and mononuclear/macrophage cells in STAD. Subsequently, RETN and related genes were analyzed from the perspective of PPI and functional enrichment, and the results showed that these genes/proteins were mainly involved in regulating hormone secretion and insulin response. Finally, RETN is also closely associated with immune cells in STAD. Conclusions RETN is a promising biomarker related to the diagnosis and prognosis of STAD, and is expected to become a new diagnostic and therapeutic target for STAD.